Technologies for converting biomass to useful energy : combustion, gasification, pyrolsis, torrefaction and fermentation - Dahlquist, Erik (Boca Raton : CRC Press, 2013)
'An important goal of the extended use of biomass is replacing fossil fuels. Potentially, all global energy needs can be covered with biomass if the utilization is efficient enough. This book provides the state of the art in the field of efficient conversion of biomass, covering most technical issues such as combustion, gasification, torrefaction, pyrolysis, pelletizing and biogasproduction. The book combines a thorough description of interesting new technologies and the basic principles and tools to be used in future process optimization work. The wide coverage of examples from all over the world will make the book important as a text book on the subject'--
Includes bibliographical references and index.
Keywords: Biomass energy; Combustion